Pengembangan Komik Audio Visual Pendidikan Pancasila Berorientasi Kearifan Lokal - Ardiawan, I Ketut Ngurah (Cetta: Jurnal Ilmu Pendidikan, 2024)
The low interest of students in the subject of Pancasila education is often perceived as monotonous and less relevant. There are also impacts caused by the lack of variation in the delivery of Pancasila material, leading students to feel bored and less interested in participating in the learning process. This highlights the need for the development of learning media that is not only informative but also engaging and contextual. This research aims to develop and test the effectiveness of local wisdom-oriented audio-visual comics for Pancasila education aimed at elementary school students. This research uses the Research and Development (R&D) method with a 4-D model, which consists of the defining, designing, developing, and disseminating stages. The research was conducted at the Gugus III Elementary School located in Tejakula District, Buleleng Regency. Data were collected through interviews, questionnaires, and observations, focusing on the feasibility, practicality, and effectiveness of the product. The results show that the developed audio-visual comics are categorized as very good, with an average feasibility score of 81.60. The practicality results from both teachers and students indicate that overall, teachers gave a score of 3.65, categorized as very practical, while students assessed it with a score of 3.84, also categorized as very practical. A significant increase was also observed in student interest after using the local wisdom-oriented audio-visual comics for Pancasila education. These findings indicate that local wisdom-oriented audio-visual comics for Pancasila education are effective in enhancing student interest in Pancasila education and are suitable for integration into the learning process in elementary schools.